Safety and tolerability of GRF6019 in mild‐to‐moderate Alzheimer's disease dementia. Issue 1 (16th December 2020) - Hannestad, Jonas; Koborsi, Katie; Klutzaritz, Vicki; Chao, Whitney; Ray, Rebecca; Páez, Antonio; Jackson, Sam; Lohr, Scott; Cummings, Jeffrey L.; Kay, Gary; Nikolich, Karoly; Braithwaite, Steven
Abstract: Introduction: This phase 2 trial evaluated the safety, tolerability, and feasibility of repeated infusions of the plasma fraction GRF6019 in mild‐to‐moderate Alzheimer's disease. Methods: In this randomized, double‐blind, dose‐comparison trial, 47 patients were randomized 1:1 to receive daily infusions of 100 mL (n = 24) or 250 mL (n = 23) of GRF6019 for 5 consecutive days over two dosing periods separated by a treatment‐free interval of 3 months. Results: The mean (standard deviation [SD]) age of the enrolled patients was 74.3 (6.9), and 62% were women. Most adverse events (55%) were mild, with no clinically significant differences in safety or tolerability between the two dose levels. The mean (SD) baseline Mini‐Mental State Examination score was 20.6 (3.7) in the 100 mL group and 19.6 (3.7) in the 250 mL group; at 24 weeks, the within‐patient mean change from baseline was –1.0 points (95% confidence interval [CI], –3.1 to 1.1) in the 100 mL group and +1.5 points (95% CI, –0.4 to 3.3) in the 250 mL group. The within‐patient mean change from baseline on the Alzheimer's Disease Assessment Scale‐Cognitive subscale was –0.4 points (95% CI, –2.9 to 2.2) in the 100 mL group, while in the 250 mL group it was –0.9 points (95% CI, –3.0 to 1.2). The within‐patient mean change from baseline on the Alzheimer's Disease Cooperative Study‐Activities of Daily Living was –0.7 points in the 100 mL group (95% CI, –4.3 to 3.0) and –1.3 points (95% CI, –3.4 to 0.7) in the 250 mL group. The mean change from baseline on the Category Fluency Test, Clinical Dementia Rating Scale–Sum of Boxes, Alzheimer's Disease Cooperative Study–Clinical Global Impression of Change, and Neuropsychiatric Inventory Questionnaire was similar for both treatment groups and did not show any worsening. Discussion: GRF6019 was safe and well tolerated, and patients experienced no cognitive decline and minimal functional decline. These results support further development of GRF6019.